T้he binding effect of constitutional court decisions on listening to facts in criminal cases of public prosecutor - Tumgum, Thanapon (Huachiew Chalermprakiet Law Journal, 2024)
Constitutional Court decisions bind parties involved in particular cases and extend a binding effect to different state bodies, including the public prosecution organization. This raises the question to what extent public prosecutors are obligated by Constitutional Court decisions when proceeding with criminal cases. Or if a constitutional case involves factual issues related to criminal cases, and the Constitutional Court has rendered decisions, to what extent are prosecutors bound by them? This article examines implications of Constitutional Court decisions on listening to facts in criminal cases of the public prosecutor, by studying principles, court judgments, and other relevant documents in Thailand, and comparing them with practices in the United States of America (US), Germany, and France. The goal is to formulate recommendations for prosecutorial conduct. Studying prosecutorial practice in the US, Germany, and France indicated that Supreme Court judgments, Federal Constitutional Court decisions, and Constitutional Council decisions in factual issues are indecisively binding on prosecutors. Prosecutors might consider different facts in criminal cases compared to constitutional cases, if different pieces of evidence or witnesses exist. In addition, prosecutors in the aforementioned countries have clear guidelines aimed at truth seeking in cases. Therefore, the public prosecution organization should clarify related regulations to boost protection of civil liberties.